A proposal for an evaluation model of pharmaceutical services for malaria Uma proposta de modelo de avaliação para a assistência farmacêutica na malária - Claudia Garcia Serpa Osorio-; Gabriela Costa Chaves; Adriana Mendoza Ruiz; Elaine Silva Miranda; Mônica Rodrigues Campos; Martha Cecília Suárez-Mútis; Letícia Figueira Freitas (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2009)
Malaria is a serious public health problem in over 90 countries worldwide. In Brazil the disease is prevalent in the Amazon and the control rationale is based on early diagnosis and treatment. Quality pharmaceutical services are considered a key element for control. A proposal for evaluating pharmaceutical services for malaria is presented here. A theoretical outline composed of a logical model and an indicator framework is discussed and strives to establish a basis for assessment and judgment of the way in which these services are actually delivered. The aim is to contribute to the understanding of pharmaceutical services for malaria and other endemic diseases, complying with the directives of the Brazilian National Medicines Policy. A malária é um grave problema de saúde pública em cerca de 90 países. No Brasil, a Amazônia congrega o maior número de casos. No país, o racional de enfrentamento se baseia em diagnóstico precoce e tratamento. A assistência farmacêutica de qualidade é considerada elemento-chave para o controle da doença. Apresenta-se uma proposta de avaliação da assistência farmacêutica, composta por um modelo lógico e uma grade de indicadores, discutidos de modo a estabelecer uma base de comparação e julgamento da forma na qual os serviços são ofertados. O objetivo é contribuir para o entendimento da assistência farmacêutica na malária e em outras endemias, atendendo às diretrizes da Política Nacional de Medicamentos.